IoT-Based Weather Monitoring Station for Smart City - Azmira, Hezry Azhar Shahiziey; Kian Sek, Tee (Evolution in Electrical and Electronic Engineering, 2022)
The idea of a "smart city" seeks to connect citizens while improving city operations and services by fusing information and communication technology (ICT) with a huge number of physical devices connected to the Internet of Things (IoT) network. One of the pillars of municipal administration is weather monitoring.  The term "weather" describes the erratic daily state of the atmosphere, which greatly impacts human activities and is significant in many different sectors. The market's present weather station, though, is pricy and inconvenient.  The objective of this project is to develop a weather station that is straightforward, inexpensive, and connected to a cloud platform in order to offer real-time notifications for climate monitoring. As a result, it might improve the accuracy of the city's data.  The Arduino Uno R3 and the ESP32-based Wi-fi module DOIT DEVKIT are the microcontrollers used in this project. The hardware in this project is separated into two categories, which are the client units and the master units. Various types of sensors are attached to the client unit, allowing all the parameters to be measured. The nine sensors linked are the temperature and humidity sensors, air quality sensors (PM 2.5 and PM 10), ultra-violet power, ultra-violet index, wind speed sensor, gas sensor, and rain sensor. The Arduino Cloud IoT platform will be used to visualize the input data after it has been sent from the client unit to the master unit. Between the client and the master unit, as a gateway, the LoRa module-equipped RF transceiver type E90-DTU (900SL30) is used. The data gathered by the sensors is then saved on the Arduino Cloud IoT platform. Using Arduino Cloud IoT, a website and mobile application was created to display real-time weather information in a graphical presentation that administrators and users could access. The surrounding weather parameters were collected by the weather sensors and the data was streamed and saved directly into the Arduino Cloud IoT platform. The data can be viewed through the Arduino Cloud IoT website and IoT Remote mobile application. The data presentation can be viewed 15 days before, 7 days before, and 1 day before instead of 1 hour and current data. Furthermore, the administrator has access to review the data collected at any moment. In analyzing the information gathered on particular locations, this initiative might be useful to some parties.